Dispersion relations of relativistic radiation hydrodynamics - Gavassino, Lorenzo (Astrophysics and space science, 2025)
We compute the linearised dispersion relations of shear waves, heat waves, and sound waves in relativistic “matter+radiation” fluids with grey absorption opacities. This is done by solving radiation hydrodynamics perturbatively in the ratio “radiation stress-energy”/“matter stress-energy”. The resulting expressions ω = ω ( k ) accurately describe the hydrodynamic evolution for any k ∈ R . General features of the dynamics (e.g., covariant stability, propagation speeds, and damping of discontinuities) are argued directly from the analytic form of these dispersion relations.